2006
DOI: 10.1016/j.mod.2006.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of XNkx2-10 expression leads to anterior defects and malformation of the embryonic heart

Abstract: Normal vertebrate heart development depends upon the expression of homeodomain containing proteins related to the Drosophila gene, tinman. In Xenopus laevis, three such genes have been identified in regions that will eventually give rise to the heart, XNkx2-3, XNkx2-5 and XNkx2-10. Although the expression domains of all three overlap in early development, distinctive differences have been noted. By the time the heart tube forms, there is little XNkx2-10 mRNA detected by in situ analysis in the embryonic heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A similar nkx2–5 dose-dependent increase in heart size was reported using zebra fish [10], although reduction in heart size and morphologic defects with further increases in nkx2–5 levels also has been reported [39]. Overexpression of Xenopus nkx2–10 has no obvious cardiac effect [3, 31]. …”
Section: Assays On the Trio Of Cardiac Nk-2 Genes In Xenopussupporting
confidence: 56%
See 1 more Smart Citation
“…A similar nkx2–5 dose-dependent increase in heart size was reported using zebra fish [10], although reduction in heart size and morphologic defects with further increases in nkx2–5 levels also has been reported [39]. Overexpression of Xenopus nkx2–10 has no obvious cardiac effect [3, 31]. …”
Section: Assays On the Trio Of Cardiac Nk-2 Genes In Xenopussupporting
confidence: 56%
“…However, in frog and chicken, it joins nkx2–5 and nkx2–10 (or Nkx2–8 in chicken) among NK-2 genes expressed in the heart. Although initial studies of nkx2–10 suggested that it was transiently expressed during early cardiac development [31, 37], a more recent analysis suggests that after a transient decrease, expression returns [3]. All the Xenopus cardiac NK-2 genes can be found in RNA isolated from adult heart, liver, and gut.…”
Section: Assays On the Trio Of Cardiac Nk-2 Genes In Xenopusmentioning
confidence: 99%
“…But, following initiation of cardiac differentiation markers, XNkx2-10 transcipts fade in the heart and remain abundant in the pharyngeal endoderm (Chambers et al, 1994; Drysdale et al, 1994). Interestingly, reduction of XNkx2-10 leads to anterior and cardiac defects during later stages of development, following looping and chamber emergence (Allen et al, 2006). Notably, the XNkx2-10 protein is more similar in length and its homeodomain is most identical to zebrafish Nkx2.7 than to the other Xenopus homologs, XNkx2-5 and XNkx2-3 (Newman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nkx2-5 +/− mice and mice carrying a hypomorphic Nkx2-5 allele exhibit less dramatic morphogenetic defects, resembling the variety of phenotypes associated with NKX2-5 mutations in patients (Biben et al, 2000; Prall et al, 2007; Stanley et al, 2002). Additional studies in Xenopus further illuminate morphogenetic functions for NKX2-5 homologs: reduction of XNkx2-10 leads to the formation of a small ventricle with impaired trabeculation (Allen et al, 2006), and expression of versions of XNkx2-5 carrying CHD-associated mutations results in problems with atrial septation, atrioventricular valve formation, and cardiac conduction (Bartlett et al, 2007). Together, these data identify a myriad of important roles for NKX2-5 -related genes during cardiac morphogenesis.…”
Section: Introductionmentioning
confidence: 99%